Effect of midwife-led pelvic floor muscle training on prolapse symptoms and quality of life in women with pelvic organ prolapse in Ethiopia: A Cluster-randomized controlled trial. - Melese Siyoum; Rahel Nardos; Biniyam Sirak; Theresa Spitznagle; Wondwosen Teklesilasie; Ayalew Astatkie (PLoS Medicine)
Background Pelvic organ prolapse (POP) is a common condition that can significantly impact a woman's quality of life. Pelvic floor muscle training (PFMT) is recommended as a first-line conservative treatment for prolapse, but evidence on its effectiveness from low-resource settings is limited. This study aimed to assess the effect of midwife-led PFMT on prolapse symptoms and health-related quality of life (HRQoL) among women with mild-to-moderate POP in Ethiopia. Methods and findings A community-based, parallel-groups, two-arm cluster-randomized controlled trial was conducted in Dale and Wonsho districts of Sidama Region, Ethiopia. Women with symptomatic POP stages I-III were randomized by cluster to receive either midwife-led PFMT plus lifestyle counseling (intervention group) or lifestyle counseling alone (control group). The participants and counselors knew what the women were receiving, but they were not aware of the other group. The outcome assessors, who collected data at the end of intervention, were blinded to the participants' treatment allocation. The primary outcomes were changes in prolapse symptom score (POP-SS) and prolapse quality of life (P-QoL). Mixed-effects generalized linear model was used to determine the effect of PFMT on prolapse symptoms and P-QoL at 99% confidence level. Adjusted β coefficients were used as effect measures. The level of significance was adjusted for multiple comparisons. A total of 187 women were randomized to intervention (n = 86) from four clusters and control (n = 101) arms from another four clusters. At sixth months, the intervention group showed significantly greater improvements both in prolapse symptoms and P-QoL. The mean change difference in POP-SS was -4.11 (99% CI [-5.38, -2.83]; p <  0.001). Similarly, the mean change difference was: -8.86 (99% CI [-13.84, -3.89]; p < 0.001) in physical domain of P-QoL; -11.18 (99% CI [-15.03, -7.32]; p < 0.001) in psychological domain of P-QoL, and -9.01 (99% CI [-10.49, -5.54]; p < 0.001) in personal relationship domain of P-QoL. A significantly higher proportion (83.72%) of women in the intervention group perceived their condition as "better" after the intervention as compared to 41.58% in the control group. Women with earlier stages of prolapse (stages I and II) experienced higher benefits compared to those in stage III. Conclusions A midwife-led PFMT combined with lifestyle counseling significantly improves prolapse symptoms and quality of life in mild-to-moderate POP. This strategy can be integrated into the existing maternal and reproductive health programs to address POP in low-income settings where access to trained specialist is limited. Trial registration The trial was registered at the Pan African Clinical Trial Registry (https://pactr.samrc.ac.za) database, with the registration number PACTR202302505126575 (https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=24311).